2019
DOI: 10.3390/cells9010026
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of CD38 and CD157 in the Solid Tumor Microenvironment and Cancer Immunotherapy

Abstract: The tumor microenvironment (TME) consists of extracellular matrix proteins, immune cells, vascular cells, lymphatics and fibroblasts. Under normal physiological conditions, tissue homeostasis protects against tumor development. However, under pathological conditions, interplay between the tumor and its microenvironment can promote tumor initiation, growth and metastasis. Immune cells within the TME have an important role in the formation, growth and metastasis of tumors, and in the responsiveness of these tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 97 publications
(260 reference statements)
0
26
0
Order By: Relevance
“…In addition to traditional pathways mediated by CD39/CD73, an alternative enzymatic cascade has been recently reported and includes ectoenzymes such as CD38 (NAD + nucleosidase), CD203α (ecto-nucleotide pyro-phosphatase phosphodiesterase 1) and CD73 (70,71), thus participating to the composition of the so-called "purinergic milieu" (72). Indeed, in the search of a better understanding of the mechanisms involved in the acquired immunotherapy resistance, it has been reported that the unresponsiveness to PD-1/PD-L1 inhibition in lung murine models is probably mediated by the tumor up-regulation of CD38 enzyme, which is induced by all-trans retinoic acid and IFN-β in the TME.…”
Section: Immunometabolism Mediated By Cd39/cd73 -Adenosine Axis In Egmentioning
confidence: 99%
“…In addition to traditional pathways mediated by CD39/CD73, an alternative enzymatic cascade has been recently reported and includes ectoenzymes such as CD38 (NAD + nucleosidase), CD203α (ecto-nucleotide pyro-phosphatase phosphodiesterase 1) and CD73 (70,71), thus participating to the composition of the so-called "purinergic milieu" (72). Indeed, in the search of a better understanding of the mechanisms involved in the acquired immunotherapy resistance, it has been reported that the unresponsiveness to PD-1/PD-L1 inhibition in lung murine models is probably mediated by the tumor up-regulation of CD38 enzyme, which is induced by all-trans retinoic acid and IFN-β in the TME.…”
Section: Immunometabolism Mediated By Cd39/cd73 -Adenosine Axis In Egmentioning
confidence: 99%
“…Compare to normal cells, though the mRNA and protein expression of CD38 was higher in malignant cells of breast cancer, lung cancer, hepatic cancer and esophageal cancer, and CD38 has been linked to the tumor differentiation, invasion and metastasis, CD38 might exhibit both stimulating and inhibiting effects to tumor development [8,[16][17][18][19]. The function of CD38 was dependent on the cancer type, tumor cell type and interaction with immune cells in the microenvironment [6,8].…”
Section: Discussionmentioning
confidence: 99%
“…CD38 is involved in regulating extracellular metabolism, intracellular Ca 2+ level, cell adhesion, activity of cyclase and hydrolytic enzyme, and signal transduction pathways, participating in the immunity regulation in tumor microenvironment (TME) [6]. CD38 has been reported to play an essential role in the primary and secondary drug resistance of ICI treatment [8]. However, the function of CD38 is complex [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATP was already shown being able to activate the VEGF receptor in the absence of VEGF, and the P2YR-VEGFR2 interaction and the resulting signal transduction are critical determinants of vascular homoeostasis and tumor-mediated angiogenesis (107). Moreover, CD38dependent signaling can impact on (tumor) angiogenesis (55,108). Herein, CD38 turned out to be an important regulator for the intrinsic expression of key angiogenic factors (100,109,110).…”
Section: The Role Of Cd39 Within Lung Tumorsmentioning
confidence: 99%